2010
DOI: 10.1186/1471-2466-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of indacaterol 150 μg once-daily in COPD: a double-blind, randomised, 12-week study

Abstract: BackgroundIndacaterol is a novel, once-daily (o.d.) inhaled, long-acting β2-agonist in development for chronic obstructive pulmonary disease (COPD). This 12-week, double-blind study compared the efficacy, safety, and tolerability of indacaterol to that of placebo in patients with moderate-to-severe COPD.MethodsEfficacy variables included 24-h trough FEV1 (mean of 23 h 10 min and 23 h 45 min post-dose) at Week 12 (primary endpoint) and after Day 1, and the percentage of COPD days with poor control (i.e., worsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 21 publications
6
107
0
5
Order By: Relevance
“…Previous study results provided an assumed treatment difference (indacaterol-tiotropium) of 40 mL for trough FEV1 at week 12 [2], with a standard deviation of 225 mL [2,11,12]. A sample size of 666 evaluable patients per treatment group was needed to detect this difference as statistically significant at the 5% level (two-sided) with 90% power.…”
Section: Methodsmentioning
confidence: 99%
“…Previous study results provided an assumed treatment difference (indacaterol-tiotropium) of 40 mL for trough FEV1 at week 12 [2], with a standard deviation of 225 mL [2,11,12]. A sample size of 666 evaluable patients per treatment group was needed to detect this difference as statistically significant at the 5% level (two-sided) with 90% power.…”
Section: Methodsmentioning
confidence: 99%
“…40 The incidence of tachycardia and tremor were found to be infrequent (2%), whereas the incidence of QTc prolongation was observed in up to 3.3% (vs. 2.0% in placebo group) of subjects, but they were not deemed to be clinically significant (<500 ms). 15,52,54,55 The study by Kerwin EM et al observed no difference in pulse and QTc intervals, but reported significant lowering in diastolic BP among subjects from the 300 mcg indacaterol group. 54 Increases in blood glucose were also observed during clinical trials.…”
Section: Indacaterol (Maleate Qab149)mentioning
confidence: 99%
“…However, most studies showed no change in potassium levels during beta-2 agonist treatment, whereas other studies observed small changes but no mention of its relationship with cardiovascular events. 51,[53][54][55] An earlier semi-open label study has reported a decrease in serum potassium levels in ~5% of subjects treated with LABAs, but no statistically significant difference was observed in laboratory values, ECG and vital signs. 38 In addition, one study has found that serum potassium and glucose levels were slightly increased without reaching significance, and incidences of other AEs were lower in the treatment group.…”
Section: Biochemistry Monitoring Of Therapeutic Efficacy and Toxicitymentioning
confidence: 99%
See 2 more Smart Citations